PENGARUH AIR REBUSAN DAUN BINAHONG TERHADAP PENURUNAN ASAM URAT - Ariani Ariani; M Syikir; Sumiyati Sumiyati; Muh Fadli; Bahtiar Yusuf (Nursing Arts, 2022)
Gout is estimated to occur in 840 people out of every 100,000 people. The prevalence of gout in Indonesia occurs at the age of under 34 years at 32% and above 34 years at 68%. Gout sufferers if not treated quickly, then the following year is expected to increase. Gout in chronic conditions causes kidney, heart, and other infections that can cause death. One of the non-pharmacological treatments in dealing with gout is by using medicinal plants, one of which is binahong (Anredera cordifolia (Tenore) Steen). The purpose of this study was to determine the effect of binahong leaf decoction on reducing uric acid in the work environment of Mapilli Polewali Mandar District Health Center. The research method is quasi experiment. The method of taking samples with consecutive sampling, the number of samples is 10 people. The results of the study obtained statistical tests using the pired sample test formula to determine the effect of giving binahong leaf boiled water on uric acid levels before and after the intervention, in getting the difference in uric acid levels before intervention had a mean of 8.33 with a standard deviation of 1.22 and a decrease after the intervention it was 7.07 with a standard deviation of 1.81. with a value of p = 0,000 (p <0.05), meaning that there is an effect of giving binahong leaf boiled water to reduce gout.